2017
DOI: 10.1152/ajpgi.00232.2016
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of gut microbiota in association between GLP-1/GLP-1 receptor expression and gastrointestinal motility

Abstract: The microbiota in the gut is known to play a pivotal role in host physiology by interacting with the immune and neuroendocrine systems in gastrointestinal (GI) tissues. Glucagon-like peptide 1 (GLP-1), a gut hormone, is involved in metabolism as well as GI motility. We examined how gut microbiota affects the link between GLP-1/GLP-1 receptor (GLP-1R) expression and motility of the GI tract. Germ-free (GF) mice (6 wk old) were orally administered a fecal bacterial suspension prepared from specific pathogen-free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 37 publications
0
35
0
1
Order By: Relevance
“…GLP-1 acts not only as an enteroendocrine hormone but also on the gastrointestinal tract, where it modulates gastric emptying and gut motility [29,32], thus also possibly contributing to weight loss [33]. These effects have also been attributed to GLP-1R expressed in the small intestine and colon in the myenteric neural cells [27] and smooth muscle [28]. We therefore decided to check whether a 10-day preventive treatment with GSPE was able to modulate GLP-1R in both the ileum and the colon and whether these long-lasting effects were partly modulated by epigenetics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GLP-1 acts not only as an enteroendocrine hormone but also on the gastrointestinal tract, where it modulates gastric emptying and gut motility [29,32], thus also possibly contributing to weight loss [33]. These effects have also been attributed to GLP-1R expressed in the small intestine and colon in the myenteric neural cells [27] and smooth muscle [28]. We therefore decided to check whether a 10-day preventive treatment with GSPE was able to modulate GLP-1R in both the ileum and the colon and whether these long-lasting effects were partly modulated by epigenetics.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, possible changes in microbiota-derived products may also be responsible. Indeed, analysis of the effect of gut microbiota on GLP-1 activity revealed that gastrointestinal motility is accelerated while GLP-1R expression is suppressed in myenteric neural cells throughout the gastrointestinal tract [27]. Short chain fatty acids are also reported to induce changes in DNA methylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Час транзиту травним трактом був значно коротшим у мишей GF з відновленою мікробіотою, ніж у контрольних мишей GF, і корелював із кількістю GLP-1R-позитивних клітин у всій стінці травного тракту. Результати засвідчили, що мікробіота кишечнику може прискорити або принаймні змінити моторику травного тракту, пригнічуючи експресію рецепторів ГПП-1 у нервових клітинах ендотелію по всьому травному тракту [48].…”
Section: Reviews / оглядиunclassified
“…On other hand, it has been demonstrated that GLP-1 is progressively up-regulated in pancreatic islets during type 2 DM development[193]. More recently, the link between GLP-1/GLP-1 receptor (GLP-1R) expression and GI motility mediated by GM has been investigated[194]. They found that the expression of GLP-1R in myenteric neural cells in the GI tract was suppressed and the GI transit time became shorter in Germ-free (GF) mice after transplantation of GM.…”
Section: Clinical Consequences Of Diabetes-induced Changes In Intestimentioning
confidence: 99%